Diabetes Self-Management Education Berbasis Experiential Learning terhadap Kepatuhan Diet dan Kualitas Hidup Pasien Diabetes - Sulistiono, Priyo; Puspitasari, Yenny; Ellina, Agusta Dian (Journal of Telenursing (JOTING), 2024)
This study aims to analyze the effect of Experiential Learning-Based Diabetes Self-Management Education (DSME) on dietary adherence and quality of life among diabetes patients at RSUD Dr. R. Koesma Tuban. A quasi-experimental method with a control group design was employed. The sample consisted of 40 respondents selected using simple random sampling. Data were collected through questionnaires and analyzed using the Wilcoxon Signed Rank Test. The results indicate that, based on the Wilcoxon Signed Rank Test with a significance level of α = 0.05, the obtained Asymp.Sig (2-tailed) value was 0.000 < 0.05, which means H1 is accepted. This finding demonstrates that Experiential Learning-Based DSME significantly affects dietary adherence and quality of life among diabetes patients at RSUD Dr. R. Koesma Tuban. In conclusion, DSME based on experiential learning has a significant impact on improving dietary adherence and quality of life for diabetes patients at RSUD Dr. R. Koesma Tuban. Keywords: Diabetes, Diet Adherence, Quality of Life, Technology